SCIENTIFIC REASONING ABILITY OF PROSPECTIVE STUDENT TEACHER IN THE EXCELLENCE PROGRAM OF MATHEMATICS AND SCIENCE TEACHER EDUCATION IN UNIVERSITY OF MATARAM - Jufri, A. W.; Setiadi, S.; Sripatmi, D. (Jurnal Pendidikan IPA Indonesia, 2016)
The purpose of this study is to investigate the scientific reasoning ability of the prospective student teacher, and to analyze the difference in scientific reasoning ability between students in the study programs. The sample set consisted of 179 students joining the Excellence Program of Mathematics and Science Teacher Education in the Faculty of Teacher Education (FTE) in the University of Mataram. The Classroom Test of Scientific Reasoning (CTSR) was translated into Indonesian language and used to measure the student scientific reasoning ability. The results of this study revealed that 95.5% students had low reasoning ability and were categorized as concrete and transitional reasoner. Only few students (4.5%) reached the category of formal operational reasoner. In addition, significant differences of the students reasoning ability emerged among the third and the fifth semester students, as well as students in the four study programs.Â